Pragmatik dan Kesantunan Berbahasa dalam Kurikulum Merdeka: Strategi Meningkatkan Kompetensi Komunikatif Siswa Sekolah Dasar: Pragmatik dan Kesantunan Berbahasa dalam Kurikulum Merdeka: Strategi Meningkatkan Kompetensi Komunikatif Siswa Sekolah Dasar - Dewi kasanti; Gresi Nurhayati Nababan; Paolina Pekei; Silvina Noviyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study examines the integration of pragmatics and language politeness into Indonesian language instruction under the Kurikulum Merdeka at the elementary school level through a library research approach and content analysis of official curriculum documents. Findings reveal that the Kurikulum Merdeka explicitly positions pragmatic competence and politeness as core learning outcomes across Phases A–C, aligning closely with Grice’s Cooperative Principle, Leech’s Politeness Principle, and Brown & Levinson’s Face-Saving Theory. The most effective strategies include project-based learning, the Strengthening Pancasila Student Profile Project (P5), role-playing, simulations, and differentiated instruction, which significantly enhance students’ communicative competence while reducing verbal conflicts by 50–70 %. The primary challenges are teachers’ limited understanding of pragmatic theory and the scarcity of context-rich teaching materials. This study recommends intensive pragmatics-based teacher training, development of dialogue-rich polite-language media, and greater parental involvement to enable the Kurikulum Merdeka to successfully produce elementary students who are not only linguistically proficient but also polite, empathetic, and capable of dignified communication in the digital era.